1998
DOI: 10.1002/(sici)1097-0290(19980620)58:6<642::aid-bit10>3.3.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of interferon‐γ sialylation in Chinese hamster ovary cell culture by feeding of N‐acetylmannosamine

Abstract: Because the presence of sialic acid can extend circulatory lifetime, a high degree of sialylation is often a desirable feature of therapeutic glycoproteins. In this study, the incomplete intracellular sialylation of interferon-gamma (IFN-gamma), produced by Chinese hamster ovary cell culture, was minimized by supplementing the culture medium with N-acetylmannosamine (ManNAc), a direct intracellular precursor for sialic acid synthesis. By introducing 20 mM ManNAc into the culture medium, incompletely sialylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
79
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 0 publications
6
79
2
Order By: Relevance
“…The results showed a linear correlation between the time period of glucose depletion during 24 h and galactosylation and sialylation indexes, suggesting that the decrease in galactosylation and sialylation could be elicited by depletion of activated monosacharides as dolichol phosphate or nucleotide derivates, mostly glucose-derived substrates. Previous studies revealed that feeding N-glycosylation precursors or substrates could improve sialylation or galactosylation of interferon-γ expressed in CHO (Gu and Wang, 1998;Jones et al, 2010). In addition, a feeding regime of uridine, manganese and galactose as media supplements improves GI of CHO-EG2 cells (Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed a linear correlation between the time period of glucose depletion during 24 h and galactosylation and sialylation indexes, suggesting that the decrease in galactosylation and sialylation could be elicited by depletion of activated monosacharides as dolichol phosphate or nucleotide derivates, mostly glucose-derived substrates. Previous studies revealed that feeding N-glycosylation precursors or substrates could improve sialylation or galactosylation of interferon-γ expressed in CHO (Gu and Wang, 1998;Jones et al, 2010). In addition, a feeding regime of uridine, manganese and galactose as media supplements improves GI of CHO-EG2 cells (Liu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…ManNAc is incorporated into mammalian cells easily rather than Neu5AC in culture conditions (51). In the cells, at least, two molecules recognize ManNAc: glucosamine (UDP-N-acetyl)-2-epimerase/N-acetylmannosamine kinase and GlcNAc 2-epimerase.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 We therefore extensively investigated the effect of exogenous ManNAc (in concentrations ranging from 2 to 50 mmol/L) on sLe x expression in cultures of patient granulocytes and monocytes using incubation times of 12 to 72 hours. In neither case did the sialic acid precursor increase sLe x expression (not shown).…”
Section: Discussionmentioning
confidence: 99%